Robot-assisted natural orifice transluminal endoscopic surgery for hysterectomy - Chyi-Long Lee; Kai-Yun Wu; Hsuan Su; Chien-Min Han; Chen-Ying Huang; Chih-Feng Yen (Elsevier, 2015)
Objective: To describe the surgical procedures of robot-assisted natural orifice transluminal endoscopic surgery (NOTES) for hysterectomy and to evaluate its feasibility. Materials and methods: From December 2014 to February 2015, four patients with benign diseases who were eligible for robot-assisted NOTES at Chang Gung Memorial Hospital were recruited to this study. Intraoperative and postoperative surgical outcomes were evaluated. Results: Robot-assisted NOTES hysterectomy was successfully performed in all these patients. None of the patients had vaginal delivery, with two being nulliparous. The mean ± standard error of the mean uterine weight was 365.5 ± 69.2 g, the mean operative time was 198.8 ± 39.0 minutes, the mean docking time was 38.3 ± 2.4 minutes, the mean blood loss was 180.0 ± 56.1 mL, and the mean postoperative hospital stay was 2.5 ± 0.3 days. The final pathologic diagnoses were adenomyosis and/or leiomyomas. Conclusion: The novel robot-assisted NOTES technology created scarless skin wounds. More importantly, the device allows the surgeon to reach deeper places to achieve hemostasis, and perform surgery on larger tumors using the curved cannulae-wristed instrument. However, its implementation is limited by the lack of appropriate instrumentation, which requires further development and break through. At this stage, robot-assisted NOTES is only useful for limited applications in highly selected patients.